Percurso etnomatemático: das narrativas de pescadores para o ensino e aprendizagem do conceito de função na Educação de Jovens e Adultos - BRABO, Madson Sanches (Universidade Federal do Pará, 2025)
This is a qualitative field research project whose aim is to structure a sequence of activities from the perspective of ethnomathematics, based on the narratives of artisanal fishermen, for the teaching and learning of the concept of function in Youth and Adult Education. Thus, the guiding question: What potential can be seen in the use of fishermen's narratives from the perspective of ethnomathematics to contribute to the teaching and learning of function in the first stage of secondary education in the EJA? Methodologically, this research took place in two stages, so that in the first stage, data was collected from three artisanal fishermen from the city of Gurupá-Pá, based on audio and video recordings of their accounts of activities related to fishing, especially the construction and manipulation of mesh nets to catch the fish called 'Dourada'. The second stage was the showing of the footage produced in the first stage of the research to students in the first stage of secondary school in Youth and Adult Education, so that, based on Ethnomathematics as a teaching and research method, we sought elements to explore the concept of function in activities that are part of these students' culture. The results highlight the potential of using strategies that involve cultural actions recognized and practiced by the students in order to understand elements belonging to the concept of function, such as variables, quantities, dependence between quantities and regularity, which are important for understanding and progressing with studies on the concept of function. In this sense, based on the results and the path made possible by this research, an educational product was produced entitled “Exploring the concept of function: Mathematics present in the practice of fishing”, which refers to a didactic guide with the potential to be used by teachers to explore the concept of function in EJA-high school classes. We consider the need for teachers' actions to be guided by and value the cultures in which they are inserted, seeking to interweave culturally shared knowledge inside and outside academia, in a dialogical perspective, without hierarchizing knowledge.